Environment and livelihoods in tropical coastal zones: managing agriculture-fishery-aquaculture conflicts (CABI head Offiice, 2006)
This book focuses on the challenges people face in managing agricultural crops, aquaculture, fisheries and related ecosystems in inland areas of coastal zones in the tropics of Asia, Africa, Australia and South America. These challenges can create conflicts in the use of natural resources between different stakeholders. Through many case studies, the book discusses the nature of the conflicts and identifies what is known and not known about how to manage them. For example, some case studies relate to the trade-offs between enhancing agricultural production by constructing embankments to keep out saline water and maintaining not only the variety of rural livelihoods but also brackish aquatic biodiversity. Other case studies provide the lessons learnt from the conversion of mangrove forests to shrimp farms.